Effect of Fermentation with Two Molds on Characteristics of Chicken Meat. (10th February 2021) - Guo, Liping; Li, Yan; Ding, Shengchao; Wang, Baowei; Zhu, Yinglian; Pang, Bin; Huang, Ming; Ho, Harvey; Yu, Jiying; Sun, Jingxin
Abstract : In the present study, we investigated the characteristics of chicken meat fermented with Penicillium nalgiovense and Penicillium chrysogenum . Hardness and springiness gradually decreased, while gumminess gradually increased during fermentation. Fermentation with P. chrysogenum led to higher hardness and lower gumminess than fermentation with P. nalgiovense . Fermentation with two molds resulted in similar microstructure, such as granule formation and fractured myofibril. The highest percentage of secondary structure was ɑ -helix, and tyrosine residues were buried after fermentation. P. nalgiovense -fermented samples contained more bound water, lower relative content of alkanes, and higher relative content of aldehydes than P. chrysogenum -fermented samples.